Pengaruh Perceived Credibility, Trust, Subjective Norms, Perceived Behavioral Control, dan Perceived Expertise terhadap Attitude toward the Influencer dan kaitannya dengan Purchase Intention pada Doctor Influencer Avoskin - Putra, Afwin Purnama; Dewi, Citra Kusuma (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Influencer marketing is an effective strategy in the digital era, the use of doctor influencers in skincare promotions increases sales and purchasing intention. Doctors are the most trusted figures in providing health solutions in Indonesia. This study aims to determine and see the effect of perceived credibility, trust, subjective norms, perceived behavioral control, and perceived expertise on attitudes toward the influencer and the effect of attitudes toward the influencer on purchase intention. The method used in this study is descriptive and quantitative, with the contribution of 400 audience respondents who have watched Avoskin promotions using doctor influencers as talents or brand ambassadors for their promotions. The sampling technique used is non probability sampling with a purposive sampling type. Data processing and analysis techniques use PLS-SEM on the SmartPLS 4.0. The results of this study indicate that there is a favorable correlation between perceived credibility, trust, subjective norms, perceived behavioral control, and perceived expertise, on attitudes toward the influencer, which have an impact on the positive attitude of the audience towards product promotions using doctor influencers. In addition, the correlation of attitudes toward the influencer to purchase intention triggers the emergence of audience purchase intentions for products promoted by doctor influencers.